Synthesis of carbon materials with different morphologies by solvothermal method with premixing. (8th March 2019) - Shi, Qin; Dong, Kun; Zhang, Liangliang; Luo, Yong; Chu, Guangwen; Zou, Haikui; Sun, Baochang
Abstract : This work presents a study on the synthesis of nanostructure carbon materials by the solvothermal method. Carbon materials with different morphologies, including chain‐like solid carbon particles, hollow carbon nanospheres, and carbon nanoribbons were obtained by adjusting operating conditions. The prepared carbon nanospheres with amorphous structures include amorphous chain‐like solid carbon particles with an average particle size of 118 nm and a length range of 300–600 nm, hollow carbon nanospheres with an average diameter of ∼533 nm, and carbon nanoribbons with an average width of ∼56 nm and a length of 1000–2000 nm. In addition, a possible growth mechanism of nanostructure carbon materials prepared by the solvothermal method was discussed. The research gives a simple route to obtain carbon materials with different morphologies.